(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Despite the high acceptability of Allium sativa (Garlic) as a remedy for many diseases as earlier stated by many researchers, previous studies have shown that chronic and unregulated consumption of garlic may result to intra vascular haemolytic anaemia in rats. The present study was conducted to examine the effect of crude extract of garlic on microscopic status of red blood cells and some other haematological indices of normal albino rats. The animals were grouped into two; group 1 were normal animals treated with water while group 2 were normal animals administered 150mg/kg body weight of crude extract of garlic on alternate days for three weeks. At the end of three weeks treatment, blood samples obtained from the tail vein of the rats were used for haematological indices and erythrocyte morphology. The values obtained were expressed as Mean± SEM and compared using student t test. The results showed that there was no significant difference in the PCV which was 43.20 ± 0.80% and 45.00 ± 0.36% in both control and experimental groups respectively. However, the RBCs were significantly decreased (P< 0.05) from 166.80 ± 3.44 x106 μL-1 in the control group to 87.80 ± 9.34 x106 μL-1 in the treatment group. The percentage reticulocyte counts on the other hand significantly increased from 2.60±4.25% in control group to 11.20± 16.4% in treated group. Fragmented RBCs with a lot of schistocytes with adequate platelets were seen on peripheral blood film of crude garlic treated rats as compared to control. Our results suggested intravascular haemolysis and numerous reticulocytes on blood film confirmed our view on bone marrow response. The presence of schistocytes and acanthocytes may be an indication that the liver is involved in the observed effect.